A critical analysis of the recent change to the unilateral foreign employment income tax exemption in South Africa and its cross-border interaction - Africa, Lee-Ann (Department of Finance and Tax, 2022)
South Africa is at the forefront of implementing the Multilateral Convention to Implement Tax Treaty Related Measures of the OECD to prevent base erosion and profit shifting (MLI), the Base Erosion and Profit Shifting Project (BEPS) recommendations and the tackling of double non-taxation. In 2017, the National Treasury announced that the tax exemption for South African expatriates would be changing. The section would be amended so that foreign employment income would no longer be fully exempt in the hands of a resident. The section 10(1)(o)(ii) exemption in its original form was the relief mechanism for residents to prevent the possibility of double taxation on the employment income derived from working outside the republic. This being when South Africa converted from a source based to a residence-based tax system on 1 March 2001, and all South African residents became subject to tax on their world-wide income. Residents working abroad were at the risk of being subject to taxation on their employment income derived in two or more jurisdictions. Residents making use of the full tax exemption in terms of Section 10(1)(o)(ii) of the Income Tax Act and rendering services in countries where no employment tax was imposed or imposed at significantly low rates has therefore resulted in double non taxation. In 2017, South Africa's National Treasury published the Draft Taxation Laws Amendment Bill, initially repealing the foreign employment income exemption entirely. However, as a result of strong criticism in the form of public commentary, National Treasury proposed and later enacted an alternative amendment by reverting to the partial repeal of the foreign employment income exemption in the form of an ‘exemption threshold'. As per the enactment of the Taxation Laws Amendment, Act, No.17 of 2017 which has revised the Income Tax Act No.58 of 1962 (IT Act), specifically with reference to the wording of section 10(1)(o)(ii) to allow for R1 million of foreign remuneration to be exempt from tax in South Africa if the individual is outside of the Republic for a stipulated number of days. The legislative amendment came into effect on 1 March 2020 and states that South African tax residents abroad will be required to pay tax up to 45% on their foreign employment income, where it exceeds the R1million threshold. With the recent budget speech in 2020, the specific tax exemption has been increased to R1.25 million. This ‘exemption threshold' primarily aims to target high net worth individuals and thus still provide the relief to middle and lower income earners. The effect of the amendment would be that all residents working outside of the Republic and who derive foreign employment income in excess of R1.25million and who have previously enjoyed the benefit of the section 10(1)(o)(ii) exemption will now be subject to taxation and possibly double taxation and would need to seek relief elsewhere if necessary. In this minor dissertation we have considered the effect of the Section 10(1)(o)(ii) amendment and what this will mean for the individual working abroad in relation to domestic tax legislation and any double tax treaties (DTC's) in place. A key finding arising from the research in the minor dissertation is that many South African's have hastily made a decision to formally emigrate through the South African Reserve Bank (SARB) procedures in an effort not to pay income tax in South Africa on foreign remuneration earned overseas. However, in considering alternate mechanisms, such as applying the rebate afforded in section 6quat of the IT Act or applying a DTC if in place, may be a simpler and more cost-effective solution instead of taking a more drastic decision to emigrate. Further, the fact that an individual potentially could be subject to tax on the full remuneration if they make the decision to formally emigrate as opposed to maintaining South African residency and only paying tax on the excess remuneration above the threshold should be considered in any future tax planning.